DprA Is Essential for Natural Competence in Riemerella anatipestifer and Has a Conserved Evolutionary Mechanism - Huang, Li; Tian, Xiu; Liu, Mafeng; Wang, Mingshu; Biville, Francis; Cheng, Anchun; Zhu, Dekang; Jia, Renyong; Chen, Shun; Zhao, Xinxin; Yang, Qiao; Wu, Ying; et al. (Frontiers in Genetics, 2019)
Riemerella anatipestifer ATCC11845 (RA ATCC11845) is naturally competent. However, the genes involved in natural transformation in this species remain largely unknown. Bioinformatic analysis predicts that DprA of RA (DprARa) has three domains: a sterile alpha motif (SAM), a Rossmann fold (RF) domain and a Z-DNA-binding domain (Zα). Inactivation of dprA abrogated natural transformation in RA ATCC11845, and this effect was restored by the expression of dprA in trans. The dprA with SAM and RF domains of Streptococcus pneumoniae and the dprA with RF and Zα domains of Helicobacter pylori was able to restore natural transformation in the RA ATCC11845 dprA mutant. An Arg123 mutation in the RF domain of R. anatipestifer was not able to restore natural transformation of the RA ATCC11845 dprA mutant. Furthermore, DprAR123E abolished its ability to bind DNA, suggesting that the RF domain is essential for the function of DprA. Finally, the dprA of Fusobacterium naviforme which has not been reported to be natural competent currently was partially able to restore natural transformation in RA ATCC11845 dprA mutant. These results collectively suggest that DprA has a conserved evolutionary mechanism.